Clean and Sustainable Groundwater in India (Springer Hydrogeology,, 2018)
The book embodies the groundwater issues and challenges in India focusing its sustainable use. It is a compilation of papers presented by the eminent experts from Government departments, academia, research institutes, NGOs and stakeholders who assembled at Kurukshetra on 21st August, 2015 in the event of Bhujal Manthan or "Churning of Groundwater" organized for the first time by Ministry of Water Resources, River Development and Ganga Rejuvenation, the apex Ministry of Water Resource under Government of India. India, as a country, is the highest groundwater extractor in the world. Its service towards attaining the food and clean drinking water security is well documented. This volume addresses the issues of aquifer characterization, groundwater contamination, groundwater resource availability and its sustainable management through community participation in pan-India scenario. This book provides a unique opportunity for its readers to understand groundwater domain in India in its entire gamut. The papers included in the volume were selected carefully from the presentations made in the following four broad topics during the Manthan; (i) groundwater quality, (ii) conjunctive use of surface and groundwater, (iii) management intervention and sustainable use of this resource, and (iv) groundwater problems and application of various techniques. The book contains 20 papers including an introductory chapter by the editors. The content of the book is enriched by contributions from eminent researchers and activists in groundwater domain, like Prof. Tushar Shah, Prof. K J Nath, Prof. Himanshu Kulkarni, Dr. D K Chadha, Dr. Bharat Sharma and others. The recommendations in the individual papers are of immense significance for keeping the groundwater of the country clean and sustainable. The volume will help the readers to understand the groundwater issues of the country and also assist policy makers to prepare strategies for its better governance and management with environmentally sustainable ways.